FAKTOR-FAKTOR YANG MEMPENGARUHI KOMITMEN ORGANISASI KARYAWAN ALFAMART DI WILAYAH KABUPATEN KARANGANYAR - Praptiestrini . (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
This research aims to analyses (1) effect of motivation on organizational commitment (2) effect of job satisfaction on organizational commitment (3) effect of work environment on organizational commitment. This research using samples of 84 employee of Alfamart in Karanganyar District area. To test the hypothesis using regression analysis. The result shows that (1) motivation have significance effect on organizational commitment (2) job satisfaction have significance effect on organizational commitment (3) work environment have significance effect on organizational commitment. This finding has a strategic implication for leaders, to develop organizational commitment of company employees need to increase employee motivation and job satisfaction and also support the creation of aconducive environment.